EDUCATION DEPARTMENT POLICY IN INTERNAL SUPERVISION OF THE DISTRIBUTION OF SCHOOL OPERATIONAL ASSISTANCE FUNDS BASED ON MINISTER OF EDUCATION AND CULTURE REGULATION NUMBER 8 OF 2020 ABOUT REGULAR BOS TECHNICAL GUIDELINES - Siregar, Vivi Arfiani; Jamri, Jamri (Yayasan Education and Social Center, 2024)
Accountable management of BOS funds means that in managing BOS funds, schools can be accountable for the use of BOS funds to the government and the community. Transparency and accountability in the use of BOS funds to the public is a form of control from the community, because the community is a component that plays an important role in the implementation of education. The main problem is the policy of the Education Service in Internal Supervision of the Distribution of School Operational Assistance Funds Based on Minister of Education and Culture Regulation Number 8 of 2020 concerning Regular BOS Technical Guidelines and the efforts and actions of the role of the Education Service in internal supervision of the distribution of school operational assistance funds based on Minister of Education and Culture Regulation Number 8 of 2020 concerning Regular BOS Technical Guidelines. Judging from its type, this research is sociological or empirical legal research ( survey ) using primary data obtained directly in the field or on direct problems. Problems that arise in the management of BOS funds have indeed been pointed out in several places, but of course this cannot be generalized in all places and conditions where abuse of authority occurs, but if we look at it in terms of opportunity or opportunity, there are many opportunities that can be used by individuals to can commit fraud